Amlodipine and frusemide: pharmacological factors contributing to increased fall risk in concurrently treated patients – a retrospective cross-sectional study - Aymen Alqurain; Murtada Albaharnah; Samanah Al Zayer; Maha Alanzi; Maha Alanzi; Razan Alblushi; Razan Alblushi; Rawan Aleid; Rand Ashoor; Ali Albahrani; Mustafa Almahdi; Samaher Al-Shaibi; et al. (Frontiers in Pharmacology, 2025)
BackgroundCalcium channel blockers, such as amlodipine, are commonly prescribed for hypertension but can cause peripheral edema, often requiring adjunctive frusemide. Concerns exist regarding the potential increase in fall risk, particularly in older populations. However, few studies have assessed the prevalence of amlodipine and frusemide combination (AFC) prescriptions and their association with fall risk factors.ObjectivesThe aims of this study are to determine the prevalence of AFC prescriptions and evaluate their association with fall risk factors in an outpatient cardiology clinic population.MethodsThis retrospective, cross-sectional study included patients aged ≥40 years from Al-Qatif Central Hospital’s outpatient cardiology clinic (January 2021 -December 2022) prescribed amlodipine. Fall risk factors were identified from literature. The Charlson Comorbidity Index (CCI) was used to estimate 1-year mortality risk. The number of prescribed orthostatic hypotension-inducing drugs (OHDs) and fall-risk increasing drugs (FRIDs) was recorded. Binary logistic regression was performed to determine the association between AFC prescriptions and fall risk factors, adjusting for significant covariates. Results are expressed as adjusted odds ratios (OR) with 95% confidence intervals (CI).ResultsOf 3,681 patients, 18%. Were prescribed AFC. AFC patients were older (70 vs. 64 years, P < 0.001), had a higher prevalence of diabetes mellitus (64% vs. 44%, P < 0.001), anemia (55% vs. 32%, P < 0.001), and osteoporosis (51% vs. 28%, P < 0.001), and received more OHDs prescriptions (2.8 vs. 1.3, P < 0.001) compared to non-AFC patients. Higher CCI scores (OR = 1.51, 95% CI 1.41–1.62) and more OHDs prescriptions (OR = 2.5, 95% CI 2.3–2.7) were significantly associated with AFC prescriptions.ConclusionAFC prescriptions are prevalent, and patients prescribed AFC have higher prevalence of fall risk factors. Comprehensive patients assessment is essential to minimize fall risk and related complications.